Nanoindentation based on force spectroscopy with an atomic force (2008)
An implementation of the method for surface indentation based on Atomic Force Microscopy (AFM), is presented. The implementation was done using the Force Spectroscopy (FS) usually enabled on this instruments which allow vertical movement of the AFM tip without lateral displacement. Determination of the sensitive factor of the AFM cantilever was necessary to know the applied forces in the indentation process. Force versus depth curves similar to Depth–Sensing Indentation (DSI) curves were obtained however these cannot be used for mechanical diagnostics with Oliver & Pharr method. Indentations about 1 nm and 50 nm of depth on polycrystalline Silicon and 6261 Aluminium alloy respectively were produced. These open important applicationsin materials nanotechnology.